(untitled) (Research, Society and Development, 2021)
The study aimed to identify the perception of university students in the health field about the attitude of voluntary blood donation. The nature of the study is exploratory-descriptive, with a qualitative approach, developed in the year 2020, with students in the health area of ​​a public university in Ceará. The data were obtained through a virtual questionnaire and interpreted according to the categorical analysis technique. The results were presented through two categories derived from content analysis, namely: 1. Blood donation as an act of solidarity and love that saves lives; 2. Need for blood donation in situations involving accidents, illnesses and surgeries. Subsequently, they were discussed using the scientific literature relevant to the subject under study. According to the results found, it was possible to conclude that although most academics are not blood donors, they recognize blood donation as a voluntary, supportive and altruistic attitude that has the ability to save lives, and is widely used in medical procedures, illnesses and accidents, which is usually necessary in blood transfusions.